Effect of land rehabilitation measures on soil organic carbon fractions in semi-arid environment - Mutio, James Mumo; Kebeney, Syphyline; Njoroge, Ruth; Churu, Harrison; Ng'etich, Wilson; Mugaa, Denis; Alkamoi, Boniface; Wamalwa, Fred (Frontiers in Sustainable Food Systems, 2023)
Soil erosion is a threat to the sustainable intensification of food systems among the smallholder farmers in the aid and semi-arid lands (ASLs). Scaling up the adoption of these measures is dependent on scientific evidence of their contributions to the key components responsible for sustainable intensification such as soil organic carbon. However, there exists little information on how existing measures influence soil carbon fractions and carbon management indices. Thus, this study focuses on evaluating the influence of soil conservation on the stated aspects in semi-arid environments . The study evaluated vegetation cover with and without terracing. The findings indicated that combined terracing and cover cropping significantly increased total organic carbon (TOC). The highest TOC of 13 gkg-1 was recorded in pasturelands with terraces while degraded land with no intervention was found to have the lowest TOC of 6.0 gkg-1. Terraced farms with long residence time (> 4 years after construction (YAC)) were found to have significantly high organic carbon than <4YAC. Labile OC and non-Labile OC significantly varied within and across combined measures, p<0.05. Pasture and crop systems with terrace record high labile OC content of 5.9 gkg-1 and 7.2 gkg-1 respectively. Labile OC across YAC followed the TOC trend i.e., it dropped from 5YAC to 1YAC. Combined pasture and terraces were found to have a significantly higher CMI of 161.7 which was 14 (fourteen) times the carbon management index (CMI) found in degraded systems with no interventions and 1.5 times the combined crop system with terraces. CMI was also directly correlated with residence time terrace had stayed in the crop system. It declined from 5YAC to 1YAC. Contrary to CMI and other indices, the weighted enrichment ratio was found to inversely correlate with YAC. Improvement of carbon content and CMI as a result of restorative measures lead to improvement in soil quality and ecosystem functions. Although terraces play a significant role in the restoration of degraded soils as indicated by the above-mentioned changes, the structures are most beneficial when used in croplands because of the high disturbances and fluctuations in input-output organic carbon.